1998
DOI: 10.3354/dao033025
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and antigenic characteristics of a cultured Rickettsiales-like organism isolated from farmed Atlantic salmon Salmo salar in eastern Canada

Abstract: The present study describes culture, virulence and antigenic characteristics of a Rickettsiales-like organism (RLO) associated with mortality in farmed Atlantic salmon in eastern Canada. Clinical disease was reproduced in naive Atlantic salmon parr by intraperitoneal (IP) inoculation with kidney homogenate from naturally infected fish. Pure cultures of RLO were isolated into chinook salmon embryo (CHSE) cells from kidney of experimentally infected fish. The RLO caused cytopathic effect in cultured CHSE-214 typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…About half of these were reported in the United States (G. S. Visvesvara, personal communication). Although CNS infections due to Acanthamoeba and Balamuthia have been recorded in animals, such as dogs, sheep, cattle, primates, and horses, 1,4,[9][10][11]15,16 there has been only 1 report of naturally acquired PAM in animals, namely in a South American tapir at a zoo in Arizona. 6 Primary amoebic meningoencephalitis has been experimentally induced in mice, sheep, and monkeys.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…About half of these were reported in the United States (G. S. Visvesvara, personal communication). Although CNS infections due to Acanthamoeba and Balamuthia have been recorded in animals, such as dogs, sheep, cattle, primates, and horses, 1,4,[9][10][11]15,16 there has been only 1 report of naturally acquired PAM in animals, namely in a South American tapir at a zoo in Arizona. 6 Primary amoebic meningoencephalitis has been experimentally induced in mice, sheep, and monkeys.…”
mentioning
confidence: 99%
“…5,11,12,16 Piscirickettsiosis or piscirickettsiosis-like syndromes can be severe, resulting in high mortality and significant economic losses.…”
mentioning
confidence: 99%
“…Piscirickettsiosis or salmonid rickettsia1 septicemia soon became evident in other salmonids (Atlantic salmon Salmo salar and rainbow trout Oncorhynchus mykiss) in both the northern and southern hemispheres (Fryer & Lannan 1996, Almendras & Fuentealba 1997, Olsen et al 1997, Jones et al 1998. The microbial etiology of these outbreaks has been confirmed by determination of close phylogenetic affiliations to Piscirickettsia salmonis LF-89 (Mauel et al 1996(Mauel et al , 1999, serological criteria (Olsen et al 1997) and comparative biochemistry of the microbial antigens (Jones et al 1998).…”
Section: Introductionmentioning
confidence: 92%
“…The microbial etiology of these outbreaks has been confirmed by determination of close phylogenetic affiliations to Piscirickettsia salmonis LF-89 (Mauel et al 1996(Mauel et al , 1999, serological criteria (Olsen et al 1997) and comparative biochemistry of the microbial antigens (Jones et al 1998). However, severe epizootics of P. salmonis occur only in the fish farms of southern Chile, while outbreaks of the organism in other parts of the world have been less pronounced and sporadic (for reviews, see Fryer & Lannan 1996, House et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, as a simple first step in evaluating any potential variation in virulence, parallel TRLO challenges could be performed using standardised doses and environmental conditions. Serotypic diversity amongst TRLO isolates is novel in that to date there is no evidence of such variation within the P. salmonis species despite its antigenic characterisation (Kuzyk et al 1996, Barnes et al 1998, Jones et al 1998. There is evidence of differences in virulence be tween P. salmonis isolates (House et al 1999), but antigenic variability has yet to be identified.…”
mentioning
confidence: 99%